Profil Kompetensi Guru dalam Pembelajaran Daring Matematika pada Masa Pandemi Covid-19 di Kelas Tinggi - Wati, Rika Kurnia; Slamet, St Y; ., Anesa Surya (Jurnal Pendidikan Dasar, 2021)
Research has been carried out that aims to describe the pedagogical competence of teachers in planning, implementing, and conducting online learning assessments of mathematics in the high class of SDI Unggulan Al Azhar Klaten. This research uses a qualitative approach with a case study method. The sample used in this research is purposive sampling taken is high class teachers and school principals. Collecting data in this study is by observation, interviews, and documentation, as well as using the validity test of triangulation techniques and sources. Data analysis in this study used the interactive model of Miles, Huberman and Saldana. The results of this study, the pedagogic competence of high-grade mathematics teachers in planning, implementing, conducting assessments still tend to be lacking and not in accordance with Permendikbud number 14 of 2019 concerning the simplification of lesson plans from 13 components into 3 core components consisting of objectives, learning activities, and assessments. as well as other complementary components. The conclusion of this study, the pedagogic competence of high-grade mathematics teachers tend to have not met all the indicators of success in learning planning, learning implementation, learning assessment. The pedagogical competence skills of high-grade mathematics teachers in planning, implementing, and conducting assessments tend to be less appropriate and need to be further improved by conducting one of them continuous guidance on the development and preparation of learning and with training.